ANALISIS MANFAAT INTERAKSI TEMAN SEBAYA TERHADAP PERILAKU SOSIAL ANAK USIA DINI DI RA MUSLIMAT NU 007 GANDU 1 MLARAK KABUPATEN PONOROGO PROVINSI JAWA TIMUR - Nuning Farida; Devi Anggi Friani (Prosiding Seminar Nasional Multidisiplin, 2018)
The development of social behavior of children is the key in social life of society. Children who have good social behavior will easily interact with others so the children can be accepted in the environment. One effort to develop children's social behavior is through interacting with peers. This study aims to analyze the benefits of peer interaction on childhood social behavior in RA Muslimat NU 007 Gandu 1 Mlarak Ponorogo Regency East Java Province. This research is a qualitative descriptive research, data obtained through observation, in-depth interviews, and documentation. The technique of data validity using triangulation technique. Qualitative data analysis is done interactively and continuously until complete, so the data is saturated. The activities in data analysis are data reduction, data presentation and conclusion. From the results of the research can be known the benefits of peer interaction on social behavior of childhood such as, the children can learn to respect each other, have a responsibility attitude, learn to work together, share and care about the condition of other friends. They learn to empathize and start learning to help a troubled friend. Key Word : social behavior, peers, childhood